Kajian Teologis tentang Kesetiaan dalam Kitab Hosea dan Implikasinya bagi Gereja Masa Kini - Hotdina Veronika Siregar; Neli Febriyanti Adang; Malik Bambangan (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This article explores the theme of faithfullness in the book of Hosea throught a theological lens and examines its relevanse for the contemporary church. The book of the Hosea presents a powerfull potrayal of God’s unwafering faithfullnes toward his people despite their reapeted unfaithfullnes. Using the metaphor of Hosea’s marriage to Gomer, God communicates a message off steadfast love, forgiveness, and restoration. This study highlights the theological significance of divine faithfullness and its role as the foundation for relational  etichs within the community of faith. The implication for the church today include a calling to live faithfully before God, to embody restorative love in community life, and to strengh then commitmen to the covenant of faith. Faithfullnes is presented not merely as a moral virtue but as a spiritual identity to be lived out in ecclesial practice. Through exegetical analysis and contextual reflection, this articel invites the church the respond to the call of faithfullness mid the chalanges of the modern era.